The presence, morphology and clinical significance of vertebral body malformations in an Australian population of French Bulldogs and Pugs. Issue 9 (16th June 2021) - Brown, JD; Podadera, J; Ward, M; Goldsmid, S; Simpson, DJ
Abstract : Objective: To describe the incidence, morphology and clinical significance of congenital vertebral malformations (CVM) in two breeds of brachycephalic dogs presenting to a referral veterinary hospital. Design: Prospective cohort study series. Materials and methods: Forty‐nine French Bulldogs and Pugs were prospectively evaluated and placed in one of two groups based on whether or not they presented for neurological signs referable to spinal cord disease. A computed tomography (CT) of their entire spine was obtained and the presence and classification of CVM along with the degree of spinal kyphosis recorded for all dogs. Statistical analysis was performed to identify clinical associations between these factors (P < 0.05). Results: CVM were prevalent across both breeds with the French Bulldog having more malformations than the Pug (Kruskal–Wallis nonparametric analysis of variance, P < 0.0001). Breed associated vertebral malformation subtypes included butterfly subtype in French Bulldogs (Chi‐square, P = 0.0002), and transitional subtype in Pugs (odds ratio, 22.7; P = 0.000). A new subtype, dorsal wedge, was observed in 12 cases. The presence, number and subtype of vertebral malformation were not reliable for predicting the development of neurological signs across both breeds (Chi‐square, P > 0.05). However, spinal kyphosis >35° calculated via Cobb angle was associated with Pugs that had neurological deficits (Chi‐square, P = 0.028). Conclusions: Congenital vertebral malformations largely appear to be incidental findings in this population of French Bulldogs but are of more significance in the Pug breed when spinal kyphosis is >35°. French Bulldogs that have spinal cord disease and CVM are more likely to have pathology distant to CVM with intervertebral disc herniation most common.